If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 9y = 48 Solving 8x + 9y = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. 8x + 9y + -9y = 48 + -9y Combine like terms: 9y + -9y = 0 8x + 0 = 48 + -9y 8x = 48 + -9y Divide each side by '8'. x = 6 + -1.125y Simplifying x = 6 + -1.125y
| 2(n+1)+1=(2n-5)+(n-2) | | 7y-13-8=5y+9-9y | | 9(z+1)-2(z-3)=3(z-4)+3(z-2) | | 10t-22=10t-15 | | 3x^2-90x+450=0 | | 8x^2+8x-9x-9=0 | | -4t-4=-7t-4 | | (d^2-d+5)-(-d^2+d+5)= | | 120=2a-(15-7a) | | 2w-10=2w+10 | | 12p+7=-17 | | 4(3x-8)-4=4(x-3)+32 | | 3p+1=13 | | 8(3a-52)-4(2a+3)=12 | | -9n-10=-100 | | 12x+11=14x+1 | | 17t+15=11t+51 | | 6y-15=-5y+18 | | (4n-1)(2n+4)= | | 4y+4=3y-6 | | 8x+3=13+3x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)= | | 12x-10=62 | | -5(X+3)2(x-1)=-14 | | 8(2)+5= | | -9w-19=4w-6 | | -9-(4)(2)(x)=3249 | | 8x^2-21x+10=0 | | 8x^2-1x-9=0 | | 10w+16=10w+16 | | 3.2q-4.1-4.6q=-2.4q-3.2 | | 1+p+5+p=-2 |